Investigating the current business model innovation trends in the biotechnology industry - Horvath, Balint; Khazami, Nesrine; Ymeri, Prespa; Fogarassy, Csaba (Journal of Business Economics and Management, 2019)
The current trend of business model research shows an increased endeavour of conceptualizing business frameworks for circular economy (CE). While previous sustainability paradigms have failed to attract market stakeholders, their reaction differ regarding this concept. The reason is discovering that the benefits of former industrial systems have turned to be threats for modern companies. Thus, a circular transition seems beneficial not only in environmental but also in financial dimensions. Closing material and energy flows results in reduced costs and enables businesses to propose novel values to customers. The present study aims to investigate the current stage of circular transformation on a corporate level. In order to do that, it thoroughly analyses the business model evolution of an innovative and knowledge-intensive industry, biotechnology. The research employs a circular evaluation method to detect which parts of the applied business structures show the signs of transition. The findings indicate that the business innovation process in the sector is in line with the disciplines of CE. However, this phenomenon is rather the result of striving for market competitiveness, than making efforts for sustainable development. It proves the emergence of CE to be as much an economic concern as it is an environmental one.